Steel metallurgy for the non-metallurgist - Verhoeven, John D., 1934- (ASM International, 2007)
This book explains the metallurgy of steel and its heat treatment for non-metallurgists. It starts from simple concepts--beginning at the level of high-school chemistry classes--and building to more complex concepts involved in heat treatment of most all types of steel as well as cast iron. It was inspired by the author when working with practicing bladesmiths for more than 15 years. Most chapters in the book contain a summary at the end. These summaries provide a short review of the contents of each chapter. This book is THE practical primer on steel metallurgy for those who heat, forge, or machine steel.
Keywords: Steel -- Metallurgy.; Metallurgy.; elektronické knihy; electronic books